Pengaruh Pengungkapan Corporate Social Responsibility dan Kualitas Audit terhadap Biaya Utang - Yanni, Yanni; Serly, Serly; Tang, Sukiantono (Universitas Gorontalo, 2024)
This research aims to analyze the impact of Corporate Social Responsibility disclosure and audit quality on debt costs. We also use company size, return on assets, and leverage as control variables in this study. The research method employs financial data from companies published on the Indonesia Stock Exchange as the sample to be tested using panel regression. The software used includes SPSS and Eviews10. The results of this study indicate that Corporate Social Responsibility disclosure does not have a significant impact on debt costs. Meanwhile, audit quality significantly and negatively affects debt costs. The control variable results show that return on assets significantly and negatively affects debt costs, while company size and leverage do not have a significant impact on debt costs.